Australian Aboriginal women prisoners' experiences of being a mother: a review. Issue 4 (17th December 2018) - Jones, Jocelyn; Wilson, Mandy; Sullivan, Elizabeth; Atkinson, Lynn; Gilles, Marisa; Simpson, Paul L.; Baldry, Eileen; Butler, Tony
Abstract : Purpose: The rise in the incarceration of Aboriginal and Torres Strait Islander mothers is a major public health issue with multiple sequelae for Aboriginal children and the cohesiveness of Aboriginal communities. The purpose of this paper is to review the available literature relating to Australian Aboriginal women prisoners' experiences of being a mother. Design/methodology/approach: The literature search covered bibliographic databases from criminology, sociology and anthropology, and Australian history. The authors review the literature on: traditional and contemporary Aboriginal mothering roles, values and practices; historical accounts of the impacts of white settlement of Australia and subsequent Aboriginal affairs policies and practices; and women's and mothers' experiences of imprisonment. Findings: The review found that the cultural experiences of mothering are unique to Aboriginal mothers and contrasted to non-Aboriginal concepts. The ways that incarceration of Aboriginal mothers disrupts child rearing practices within the cultural kinship system are identified. Practical implications: Aboriginal women have unique circumstances relevant to the concept of motherhood that need to be understood to develop culturally relevant policy and programs. The burden of disease and cycle of incarceration within Aboriginal families can be addressed by improving health outcomes for incarcerated Aboriginal mothers and female carers. Originality/value: To the authors' knowledge, this is the first literature review on Australian Aboriginal women prisoners' experiences of being a mother.